2021
DOI: 10.1002/jgm.3328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two Chinese pedigrees with maternally inherited hypertension

Abstract: Background Mutations in mitochondrial tRNA (mt‐tRNA) genes are associated with hypertension, although their pathogenic mechanisms remain poorly understood. Methods In the present study, two Han Chinese families with maternally transmitted hypertension were interviewed. The mtDNA mutations of matrilineal relatives were screened by polymerase chain reaction‐Sanger sequencing. Mitochondrial ATP, membrane potential and reactive oxygen species (ROS) were also analyzed in polymononuclear leukocytes carrying these mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The Cell Titer‐Glo ® Luminescent Cell Viability Assay kit (Promega, Madison, USA) was used to determine the ATP production in mutant cell lines carrying tRNA mutations and the controls, using the protocol provided by the manufacturer. 33 …”
Section: Methodsmentioning
confidence: 99%
“…The Cell Titer‐Glo ® Luminescent Cell Viability Assay kit (Promega, Madison, USA) was used to determine the ATP production in mutant cell lines carrying tRNA mutations and the controls, using the protocol provided by the manufacturer. 33 …”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that the Mt3253 (T > C) mutation (tRNA Leu(UUR) ) resulted in the decreased activity of mitochondrial complexes I and V, leading to 66% lower ATP production, reduced membrane potential and the increased production of ROS [57]. Similarly, the Mt10454 (T > C) and Mt10410 (T > C) mutations significantly reduced mitochondrial ATP and membrane potential, increased ROS production and raised the levels of MDA (malondialdehyde) and 8-OhdG (8-Oxo-2'-deoxyguanosine), while levels of SOD (superoxide dismutase) and GSH-Px (glutathione peroxidase) were decreased [56]. Cell lines carrying the Mt4467 (C > A) mutation (tRNA Met ) had decreased oxygen consumption, 26.2% lower mitochondrial membrane potential, 26.4% lower ATP level, and 114.5% higher ROS production [61].…”
Section: Mitochondrial Energy Synthesismentioning
confidence: 99%
“…We compared human mtDNA nucleotide variation with 16 species to determine the conservation index (CI). 34 A CI ≥ 75% was regarded as having functional potential. 35 …”
Section: Methodsmentioning
confidence: 99%